Portofolio Optimal Saham Menggunakan Model Indeks Tunggal Studi Empirik pada Saham-Saham Jakarta Islamic Index (JII) Periode 2014-2018 - Hendrato Setiabudi Nugroho (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2020)
The purpose of this study is to form a portfolio of Sharia shares, primarily shares incorporated in the Jakarta Islamic Index (JII) using a single index. This portfolio is very important as an alternative investment in Islamic stocks on the Indonesia Stock Exchange (IDX). Similar research that has been done before only focused on conventional shares incorporated in the CSPI or LQ45. The results indicate that there are 10 leading shares included in the optimum portfolio, with the proportion of each share as follows: TLKM 40.46%, UNVR 26.62%, UNTR 10.96%, KLBF 4.59%, ASII 4.49%, INDF 3.85%, WIKA 3.44%, ADRO 3.25%, SMRA 2.01%, and AKRA 0.35%. The portfolio formed resulted in an expected return of 75.47% per year with a risk of 9.40%. Investors who tend to avoid risk (risk averse) will prefer diversification rather than investing in individual stocks.